"As aglomerações de homens de todas as classes": trabalhadores escravos e livres, brasileiros e imigrantes na construção e início da operação da São Paulo railway (1860-1872) - Andrade, Paulo Rodrigues de [UNIFESP] (2016)
The dissertation addresses the crowd of subaltern workers employed in construction and the early operation of the first railway in São Paulo, São Paulo Railway, which linked the port of Santos to Jundiaí, from 1860-1872. This crowd was made up of slaves and free workers, Brazilians and immigrants. The resulting achievement of the development of capitalism in the nineteenth century, with its implementation in Brazil still slave, was a symbiosis between slavery and railroad, what to put in discussion the paper is in the transition from slave to free. During the period of construction of the SPR, the presence of slaves in the construction sites was a constant, despite legislation prohibiting this employment. The context of the construction of the SPR was also marked by the Paraguayan War (1864-1870), an event that led to the recruitment of Brazilian workers employed in the works, despite the exemption they had for the Army and National Guard. Brazilian workers with the Portuguese made up the majority of the workforce in the works. Many conflicts involving workers and other staff of different nationalities took place. However, the main conflict was between the Brazilians and the Portuguese. At certain times, such claims as that of late payments, led the workers to come together in defense of their interests, at other times, divisions, mainly related to nationality issues just hindered the process of class identity formation among these workers, at least during the phase of construction of the railway.